0272 Finding a space for health within the context of 'occupational risk' and farm policy: ireland's 'farmers have hearts' workplace cardiovascular screening programme. (21st August 2017) - Doorn, Diana van; Richardson, Noel; Osborne, Aoife
Abstract : Background: Irish farmers are a 'high risk' group in terms of CVD mortality compared to other occupation groups. Despite CVD being recognised as a work-related condition, the focus of farmers' occupational health policy remains firmly fixed on safety rather than health. The aim of this study was to investigate the cardiovascular health status of a sub-group of Irish livestock farmers who participated in a workplace screening programme, with a view to leveraging support for an increased focus on health within the context of 'occupational risk' and farm policy. Methods: In total, 310 farmers participated in this cross-sectional study. Consent included permission to analyse farmers' cardiovascular screening results, which included cholesterol and blood glucose levels, blood pressure, and anthropometric measurements. All data were entered into the SPSS (v22) for both in-depth descriptive and inferential statistical analysis. Results: Almost one in two farmers had high blood pressure (46%; n=140) and/or raised cholesterol (46%; n=140). Four in five farmers were overweight/obese based on body mass index (86%; n=267) and waist circumference (80%; n=244) measurements. The majority of farmers were found to have at least four risk factors for CVD (83%; n=255) increasing risk of a cardiac event by 3.2 times. Discussion: This prevalence of multiple risk factors for CVD among farmers is a particular cause of concern, and sheds light on the excess burden of CVD mortality among farmers in Ireland. There is an urgent need for a broader focus on health within the context of 'occupational risk' and farm policy.